Obtención de extractos orgánicos con actividad antimicrobiana a partir de Penicillium sp. (Moniliales) aislado de la esponja Ircinia felix (Porifera: Demospongiae) - Gómez-Guiñán, Y. (2003)
This research expresses the potential of the bacterial activity present in the organic extracts obtained from Penicillium sp., isolated from the esponge Ircinia felix. This activity was evaluated through agar diffusion test and Minimal Inhibitory Concentration (MIC). The susceptibility trials of organic fractions were carried out against Staphylococcus aureus, S. epidermidis, Bacillus cereus and B. subtilis. The use of the chromatographic techniques (CLV and TLC), permitted to obtain bioactive organic extracts of different polarities, of which only the EtOAc and MeOH fractions inhibited the growth of the bacteria used. Of the EtOAc fractionation, only fraction number 3 EtOAc/Hex presented greatest activity against the Gram-positive bacteria. Number 1 EtOAc/Hex fraction increased its activity against S. aureus (24 mm) and S. epidermidis (25 mm), which can be explained by the loss of possible antagonistic effect during the fractionation process. The CMI trials were carried out for the EtOAc number 1 subfraction against S. aureus, S. epidermidis, B. cereus and B. subtilis, wich was clinical interest, and shows the potential of this organic extract as antimicrobial agent.